Energy Consumption and Sectoral Trade in Selected West African Economies (2019)
This paper examines the impact of disaggregate energy consumption on sectoral trade in selected West African countries from 1971 to 2015. Panel data analysis indicates that the effect of fossil fuel consumption on agricultural, manufactured and services exports is negative, while that of fuel export is positive. However, electricity has positive effect on the exports of three sectors, while its impact on fuel export is insignificant. Further, fossil fuel generates negative impact on manufactured and services imports, but positive and insignificant effect on agricultural and fuel exports respectively. The effect of electricity on sectoral imports is positive except for agricultural products where it is insignificant. The country level analysis reveals diverse effects of fossil fuel and electricity consumption across sectoral trade structure and the selected West African countries. The foregoing findings inform the articulation of some policy implications including the following. Energy conservation policy is required to encourage production and exporting of commodities with energy saving techniques so as to save costs, conserve non-renewable energy, and foster export diversification in the selected countries. Liberal import policy should be accompanied with energy conservation policy especially where inefficiency of non-renewable energy use is prevalent.